2017
DOI: 10.1167/iovs.16-21015
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Retinal Vasodilation in Patients With Type 1 Diabetes: A Longitudinal Study of Retinal Vascular Geometry

Abstract: Citation: Liew G, Benitez-Aguirre P, Craig ME, et al. .3) mmol/mol]) over three visits, with a mean follow-up of 2.6 years. Retinal vascular geometry was measured using a standardized computer-assisted protocol from retinal photographs at each visit. Multivariable linear mixed-models and logistic regression were used to examine predictors of RVG and diabetic retinopathy.RESULTS. During follow-up, mean arteriolar caliber, venular caliber, and venular tortuosity increased, from 156.0 (SD, 14.5) to 164.9 (14.0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…The fact that there is no association of CRVE and diabetes parameters in our patients seems to indicate that diabetes‐induced venular widening may occur later in life. In contrast to our findings, Liew et al recently found increasing CRVE in late adolescent diabetes patients . This might be explained by the slightly higher age of their subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fact that there is no association of CRVE and diabetes parameters in our patients seems to indicate that diabetes‐induced venular widening may occur later in life. In contrast to our findings, Liew et al recently found increasing CRVE in late adolescent diabetes patients . This might be explained by the slightly higher age of their subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies show that changes in macrovascular and functional parameters correlate with quality of diabetes control and conventional cardiovascular risk factors . There is growing evidence that also microvascular changes can be demonstrated in children and adolescents …”
Section: Introductionmentioning
confidence: 99%
“…A study measuring length-to-diameter ratio and simple tortuosity in type 1 diabetes found lower arteriolar length-to-diameter ratio and greater simple tortuosity predicted incident DR over a median follow-up time of 3.8 years 56 , with these findings confirmed in another study 57 . In the same cohort of type 1 diabetes patients, longitudinal changes of retinal vessel geometry were examined, they found that retinal vessels dilated and became more tortuous over 2.6year follow up 58 . The Singapore Malay Eye Study found that wider CRAE was associated with the incidence of referable DR at 6 years, as were changes in other geometric parameters.…”
Section: Sivamentioning
confidence: 99%
“…With high-resolution retinal fundus images, geometric factors of retinal vasculature such as diameter, curvature tortuosity, and branching angles can be analyzed to help assess coronary artery diseases, 1 CVDs, 2,3 or diabetes mellitus. 4 The diameters of the retinal vessels have also been shown to be associated with cognitive ability 5,6 and dementia 7 in an older population.…”
Section: Introductionmentioning
confidence: 99%